Beneficial Impacts of Solanum aethiopicum L. in Diabetes Control - Magnus Michael Chukwudike Anyakudo; Naomi Tinuola. Omogbehin; Olorunsola Israel. Adeyomoye (International Journal of Nutrition, 2022)
Garden egg nutritional values are numerous. However, few nutritional and epidemiological data exist on the impacts of garden egg consumption on diabetes control. In this experimentally-control designed nutritional study, the effects of scarlet garden egg species (Solanum aethiopicum L.) on lipoglycemic profile, weight control and, pancreas histoarchitecture in diabetic male Wistar rats were examined. Twenty-One adult male Wistar rats inducted with diabetes were randomly categorized into three groups (n = 7, each): Diabetic control (DC); Diabetic treated with aqueous extract of garden egg (DEE) and Diabetic fed with garden egg-supplemented diet (DSE). Animals were fed for six weeks according to the experimental design. Glycemic status and body weights were assessed twice weekly while lipid analysis was conducted at the entry and 6th week of the study. Oral glucose tolerance (OGT) test was conducted. Gross analysis and tissue histology of the pancreas were assessed by Hematoxylin and Eosin (H&E) staining technique. Statistical analysis was done using analysis of variance, and the results were expressed as mean ± S.E.M. at P < 0.05. Garden egg reduced mean body weight gain (DSE: 14.53%; DEE: 10.58%; P value = 0.04) and decreased blood glucose concentrations (DEE: 37.33%; DSE: 18.68%; P = 0.03) with corresponding improved lipid profile, glycemic tolerance and control (DEE > DSE) and, preserved pancreas histoarchitecture in diabetic Wistar rats. Solanum aethiopicum (garden egg) consumption (as fresh fruit or supplemented diet) preserves pancreatic tissue histoarchitecture and improves lipoglycemic profile and weight control in diabetic Wistar rats.
Keywords: Diabetic rats